Estudos das espécies Cnidoscolus quercifolius Pax et K. Hoffm E Annona muricata L. para geração de energia - Freitas, Mikael de Lima (2013)
Due to the requirement for economic sustainability, studies on the use of biomass or biofuels to energy obtention has increased in recent years. Biomass energy is obtained by burning wood, bagasse, forest and agricultural residues, among others. Nowadays, renewable resources represent about 20% of total energy supply in the world and biomass is about 14%. The production of electricity from biomass is currently advocated as very important alternative for developing countries. The present work aims to study species adaptable to northeastern of Brazil for energy generation. In this context, Cnidoscolus quercifolius (faveleira) and Annona muricata L. (graviola), are characterized as raw materials with potential use for alternative energy source. Besides the possibility of evaluating the various parts of the plant for power generation, it is possible to employ the seeds, due their high content of oil which can be used as a source of triacylglycerols for the biodiesel production.